2015
DOI: 10.1063/1.4938152
|View full text |Cite
|
Sign up to set email alerts
|

A simple structure of all circular-air-holes photonic crystal fiber for achieving high birefringence and low confinement loss

Abstract: We propose a simple structure of photonic crystal fibers (PCFs) with high birefringence and low confinement loss based on one rectangular centric ring of smaller circular air holes (CAHs) in the fiber core, and three rings of larger CAHs in the fiber cladding. This simple geometry (using all CAHs with two different air hole sizes) is capable of achieving a flexible control of the birefringence, B = 5.501 × 10−3, and ultra-low confinement loss, 7.30 × 10−5 dB/km, at an excitation wavelength of λ = 1550 nm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Due to seldom research works related to the high birefringent PCF for the application of FOG, the comparison table has been taken for more specific references which discuss the compactness of PCF with high birefringence. The proposed PCF has only circular air holes, whereas some other research works have also reported to show the impact of different types of air holes such as elliptical [45,46] and circular [18,47] to achieve high birefringence. There are number of fabrication techniques to fabricate PCF today, like sol gel casting [48], stack and draw process [49], drilling method [50], and extrusion method [51].…”
Section: Parametermentioning
confidence: 88%
“…Due to seldom research works related to the high birefringent PCF for the application of FOG, the comparison table has been taken for more specific references which discuss the compactness of PCF with high birefringence. The proposed PCF has only circular air holes, whereas some other research works have also reported to show the impact of different types of air holes such as elliptical [45,46] and circular [18,47] to achieve high birefringence. There are number of fabrication techniques to fabricate PCF today, like sol gel casting [48], stack and draw process [49], drilling method [50], and extrusion method [51].…”
Section: Parametermentioning
confidence: 88%
“…Several such PCFs that attain the abovementioned properties using all circular air holes were the subject of many studies. For example, Chau et al designed a simple PCF structure using only circular air holes and obtained birefringence of about 5.501 × 10 −3 at 1550 nm [20]. Yang et al proposed a novel PCF with all circular air holes, with two enlarged air holes in the first ring of the cladding and three shrunken air holes in the core region.…”
Section: Introductionmentioning
confidence: 99%